Perbedaan Efektivitas Terapi Musik Klasik Dan Murottal Al Qur’an Terhadap Intensitas Nyeri Disminore Pada Remaja Putri Di SMK Kesehatan Kader Bangsa Palembang Tahun 2022 - Andre Utama Saputra Utama; Ranida Arsi; Yeni Elviani (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Prevalence of dysmenorrhea According to data from the World Health Organization (WHO), there were 1,769,425 people (90%) of women who experienced dysmenorrhea with 10-15% experiencing severe dysmenorrhea. Objectives: This study aims to determine the differences in the effectiveness of classical music therapy and murottal al-Qur'an on the intensity of dysmenorrhea pain in adolescent girls. Methods: This type of research is a Quasi Experiment with a two-group pretest-posttest research method design. The population in this study were all young women who experienced dysmenorrhea pain who met the inclusion criteria of researchers, with sampling using the Lemeshow formula so that 30 respondents were obtained and divided into 2 intervention groups, namely 15 respondents in the classical music therapy intervention group and 15 respondents in the classical music therapy group. respondent group murottal al-Qur'an, the sampling technique used is purposive sampling. The research instrument used the NRS (Numeric Rating Scale) checklist sheet. Data analysis used independent T-Test test and Paired T-Test Results: The results of the Paired T-Test analysis in the classical music therapy group with a sig value of 0.041 and in the Murrotal Al-Qur'an Therapy group with a sig value of 0.002, meaning that the two intervention groups have a significant effectiveness on pain intensity in adolescent girls. The results of the independent T-Test show a p-value of 0.878, meaning that there is no difference between classical music therapy and murrotal Al-Qur'an therapy because they both can reduce the intensity of dysmenorrhea pain in adolescent girls at SMK Kesehatan Kader Bangsa Palembang in 2022